PENGARUH APLIKASI BOKASHI TERHADAP DINAMIKA KETERSEDIAAN N, P, DAN S PADA INCEPTISOL KARANGPLOSO, MALANG - Ursulin Sacer Setyastika; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
The Inceptisol of Karangploso has low soil pH, low organic matter (OM), medium total soil N, very low C/N ratio, and low available sulphur- that cause low soil productivity. The application of bokashi preserves strongly productivity and organic matter in the soil. This research aimed to determine the effect of bokashi application in improving soil chemical properties and N, P, S-available in an Inceptisol of Karangploso. The experiment was conducted in greenhouse of Facultyof Agriculture, Brawijaya University using a completely randomized design with 7 treatments and 3 replications. The treatments consisted of O1 = dose of 5 t ha-1 + ½ A, O2 = dose of 10 t ha-1 + ½ A, O3 = dose of 15 t ha-1 + ½ A, O4 = dose of 20 t ha-1 + ½ A, O5 = dose of 25 t ha-1 + ½ A, and O6 = dose of 30 t ha-1 + ½ A. The results showed that the increasing dose of bokashi significantly increased soil pH (from 5.1 to 5.4), C/N ratio (from 9.64 to 9.93), P-available (from 141 to 142.6 ppm P) at 60 DAI (days after incubation), total N (from 0.21 to 0.24% at 30 DAI and 0.18% to 0.24% at 60 DAI ) and NO3- (from 24.96 to 65.47 ppm at 30 DAI and 14.91 ppm to 39.20 ppm at 60 DAI) compared to the control, but it had no significantly effect on organic carbon, OM, SO42- in soil. The correlation test showed that there was a strong and positive correlation between pH and NO3- (r=0,77*), organic carbon and NO3- (r=0,63), organic carbon and P-available (r=0,78*), OM to NO3- (r=0,70*), and OM to P-available (r=0,86*).